Peran Teknologi Digital dalam Meningkatkan Akses Pasar Bagi Pelaku UMKM di Kota Bima - Runi Asriani; Muhammad Rasyad Al Fajar; Muhammad Zia Ulhaq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Economic actors in Bima City, especially MSMEs, have great potential to optimize digital technology to expand market access. However, the level of technology adoption among them is still relatively low, as most still rely on traditional marketing methods such as direct sales and local markets. So the research aims to determine the role of digital technology in increasing market access for MSME actors in Bima City. This research is located in Bima City, West Nusa Tenggara. The data collection techniques used are observation, interview and documentation. Then the Data Analysis Technique is Data Reduction, Data Presentation and Conclusion Drawing or Verification. Then Test Data Credibility namely Member Check, Cross Check, Triangulation and Reference Material. Based on the results of his research, it shows that digital technology now acts as a major driver in changing the way MSMEs operate in Bima City. Through the utilization of the internet, e-commerce platforms, social media, and digital payment systems, MSME players can expand market coverage without regional restrictions. This digitalization not only improves business efficiency, but also strengthens brand image and expands consumer networks, making technology an essential part of business development strategie.